2019
DOI: 10.1155/2019/2609516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 6-Month Micronutrient-Dense Plant-Rich Nutrition Intervention on Health and Well-Being at the Worksite

Abstract: This nonrandomized pilot study utilized the health belief model and the theory of planned behavior to assess the effectiveness of perceived behavioral control to determine the impact of a micronutrient-dense plant-rich (mNDPR) dietary intervention on employee health and wellness at the worksite. Seventy-one employees and/or spouses (≥18 years) who met the inclusion criteria were recruited from a regional medical center and a local university. Participants were provided more than 14 hours of in-person lecture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Dietary interventions emphasizing micronutrient-dense, plant-rich diets have shown promise in enhancing sleep quality in multiple studies. A 9-week trial of one such dietary intervention in a cohort of employees found that Pittsburgh Sleep Quality Index (PSQI) scores improved from a median score of 8 to 4, consistent with an improvement in the participants’ sleep quality ( 52 ). In another study conducted at a university setting, 35 individuals switched their diet to a micronutrient-dense, plant-rich diet for 6 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Dietary interventions emphasizing micronutrient-dense, plant-rich diets have shown promise in enhancing sleep quality in multiple studies. A 9-week trial of one such dietary intervention in a cohort of employees found that Pittsburgh Sleep Quality Index (PSQI) scores improved from a median score of 8 to 4, consistent with an improvement in the participants’ sleep quality ( 52 ). In another study conducted at a university setting, 35 individuals switched their diet to a micronutrient-dense, plant-rich diet for 6 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research indicates that wellbeing increases with overall consumption of fruits and vegetables and with increasing the number of days fruits and vegetables are consumed (15,16). Results from interventions encouraging individuals to increase consumption of plant-based food options also found positive improvements on overall mental health and wellbeing, reducing depressive symptoms and improving sleep quality (17,18). A causal relationship between a plant-based diet and positive mental health outcomes is less established, especially when compared to the extant literature that supports the positive effects of a plant-based intervention on physical health (19).…”
Section: Introductionmentioning
confidence: 96%
“…MicroNutrient-Dense, Plant-Rich (mNDPR) dietary patterns, similar to the Nutritarian dietary pattern described in this study, have been shown to be safe and effective in clinical applications and are positively associated with weight reduction, [11][12][13] lipid management, 11,12,14 glycemic control in diabetes, 15 inflammation reduction, 16 perceptions of hunger, 17 reduction in depressive symptoms and improvement in wellbeing, 11,[18][19][20] reducing the risk of developing cancer, 21 and overall health and longevity. 22 Various plant-based diets such as vegan diets and vegetarian diets have been studied extensively.…”
mentioning
confidence: 99%